Algorithmic Thinking in Secondary Mathematics Education: Challenges, Strategies, and Opportunities (Journal SCIENCEVOLUTION, 2025)
The objective of this study was to critically examine and contrast the empirical and theoretical evidence on the implementation of algorithmic thinking (AT) in secondary mathematics education, identifying patterns of efficacy, structural limitations, and proposals for improvement across diverse contexts. A literature review was conducted, analyzing 26 sources published between 2015 and 2025 from international databases linked to the development of mathematical competencies. The thematic-interpretative analysis revealed that AT constitutes an essential component of computational thinking (CT) and serves as a pedagogical strategy for systematic problem-solving, logical reasoning, abstraction, and creativity. A positive impact was identified for tools such as Scratch, robotics, GeoGebra, and WxMaxima, as well as for active and game-based methodologies that increase student motivation and skills. Conversely, the absence of AT in official curricula, a lack of teacher training, a predominance of traditional approaches focused on mechanical repetition, and technological gaps were observed to affect equity in access. In conclusion, AT is established as a relevant transversal competency for contemporary education, whose effectiveness depends on contextual factors. The promotion of inclusive policies, the development of hybrid models adapted to contexts with low connectivity, and the fostering of Latin American research are recommended.
Keywords: Algorithmic Thinking; Computational Thinking; Mathematical Skills; Secondary Education; Pedagogical Strategies